A Comprehensive Review of Portosystemic Collaterals in Cirrhosis: Historical Aspects, Anatomy, and Classifications - Cyriac Abby Philips; Ankur Arora; Rajesh Shetty; Vivek Kasana (International Journal of Hepatology)
Portosystemic collateral formation in cirrhosis plays an important part in events that define the natural history in affected patients. A detailed understanding of collateral anatomy and hemodynamics in cirrhotics is essential to envisage diagnosis, management, and outcomes of portal hypertension. In this review, we provide detailed insights into the historical, anatomical, and hemodynamic aspects to portal hypertension and collateral pathways in cirrhosis with emphasis on the various classification systems.